A Systematic Review of Behavioral Intervention Technologies for Youth With Chronic Health Conditions and Physical and Intellectual Disabilities: Implications for Adolescents and Young Adults With Spina Bifida. (18th December 2018) - Stiles-Shields, Colleen; Crowe, Autumn N; Driscoll, Colleen F Bechtel; Ohanian, Diana M; Stern, Alexa; Wartman, Elicia; Winning, Adrien M; Wafford, Q Eileen; Lattie, Emily G; Holmbeck, Grayson N
Abstract: Objective: Behavioral intervention technologies (BITs) stand as a promising delivery mechanism that overcomes multiple condition-specific and access barriers for self-management interventions for adolescents and young adults with spina bifida (AYA-SB). The purpose of the current review was to synthesize the behavioral and self-management intervention literature in conditions that have overlapping symptoms with youth with SB and to develop a model of likely user needs for AYA-SB that promotes self-management. Method: The search strategy was conducted by a medical research librarian in the following databases: MEDLINE (Ovid), EMBASE (Elsevier), PsycINFO (EbscoHost), the Cochrane Library (Wiley), and Web of Science (Thomson Reuters) databases. The review was based on a systematic narrative synthesis framework and adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (registration number CRD42018092342). Results: In total, 18 articles were included in the current BIT review. The majority of included studies (1) targeted the management of chronic health conditions, (2) were informed by evidence-based approaches, (3) relied on content delivery, (4) were Web-based, (5) used linear or user-driven workflows, (6) included professional human support, and (7) included a control condition. Conclusions: Many of the evaluated BITs resulted in acceptable usage and maintained or improved targeted symptoms. A user needs model for AYA-SB is proposed with the intention that future research will promote further refinement and ultimate deployment of a BIT for AYA-SB to promote self-management.